1993
DOI: 10.1007/bf00405728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aircraft noise on hearing and auditory pathway function of school-age children

Abstract: This study was conducted to investigate the influence of high-frequency aircraft noise on the function of the auditory system of school-age children. A total of 228 students attending a school near an airport (school A) and 151 students attending a school far from an airport (school B) were analyzed. Audiometry and brainstem auditory evoked potential (BAEP) detection were performed in all subjects to evaluate cochlear and retrocochlear function. The results of audiometry indicated that hearing ability was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
3
29
1
2
Order By: Relevance
“…Noise-induced hearing loss was reportedly higher in children who attended a school located under a flight path near a Taiwan airport compared to children at another school farther away (Chen et al 1997). Another study reported that hearing ability was reduced significantly in individuals who lived near an airport and were frequently exposed to aircraft noise (Chen and Chen 1993). In that study, noise exposure near the airport was reportedly uniform, with DNL greater than 75 dB and maximum noise levels of about 87 dB during overflights.…”
Section: B372 Health Effectsmentioning
confidence: 85%
“…Noise-induced hearing loss was reportedly higher in children who attended a school located under a flight path near a Taiwan airport compared to children at another school farther away (Chen et al 1997). Another study reported that hearing ability was reduced significantly in individuals who lived near an airport and were frequently exposed to aircraft noise (Chen and Chen 1993). In that study, noise exposure near the airport was reportedly uniform, with DNL greater than 75 dB and maximum noise levels of about 87 dB during overflights.…”
Section: B372 Health Effectsmentioning
confidence: 85%
“…The amplitude of the BERA waveforms depends on the number of neural elements activated by the sound stimulus and the degree of synchronized activity of these neural elements. [19][20][21][22] A systematic trend of decreased wave I amplitude with increasing noise exposure backgrounds (NEB) was observed by Stamper and Johnson in 2015. 23 In patients with NIHL, many authors have observed a significant extension of the waves I, III, V and I-III inter-peak latencies, 17,24 with results similar to that of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Noise-induced hearing loss was reportedly higher in children who attended a school located under a flight path near a Taiwan airport, as compared to children at another school far away (Chen et al 1997). Another study reported that hearing ability was reduced significantly in individuals who lived near an airport and were frequently exposed to aircraft noise (Chen and Chen 1993). In that study, noise exposure near the airport was reportedly uniform, with DNL greater than 75 dB and maximum noise levels of about 87 dB during overflights.…”
Section: B256 Health Effectsmentioning
confidence: 99%